2018
DOI: 10.1038/s41386-018-0173-y
|View full text |Cite
|
Sign up to set email alerts
|

The olfactory bulb is a source of high-frequency oscillations (130–180 Hz) associated with a subanesthetic dose of ketamine in rodents

Abstract: High-frequency neuronal population oscillations (HFO, 130-180 Hz) are robustly potentiated by subanesthetic doses of ketamine. This frequency band has been recorded in functionally and neuroanatomically diverse cortical and subcortical regions, notably ventral striatal areas. However, the locus of generation remains largely unknown. There is compelling evidence that olfactory regions can drive oscillations in distant areas. Here we tested the hypothesis that the olfactory bulb (OB) is a locus for the generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
31
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 54 publications
8
31
2
Order By: Relevance
“…We found that KX mitral/tufted neurons fire in phase with 80–130 Hz, consistent with a previous finding under KX reporting mitral/tufted firing over 100 Hz and associated with inhalation/exhalation transitions [Burton and Urban, 2014]. Our previous work in freely moving rats given a subanesthetic dose of ketamine also showed spiking phase locked to a fast 130–180 Hz activity [Hunt et al, 2019]. Nasal respiratory therefore provides a gate for the firing of OB projection neurons [Wachowiak, 2011] and the emergence of ketamine-dependent fast rhythms.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We found that KX mitral/tufted neurons fire in phase with 80–130 Hz, consistent with a previous finding under KX reporting mitral/tufted firing over 100 Hz and associated with inhalation/exhalation transitions [Burton and Urban, 2014]. Our previous work in freely moving rats given a subanesthetic dose of ketamine also showed spiking phase locked to a fast 130–180 Hz activity [Hunt et al, 2019]. Nasal respiratory therefore provides a gate for the firing of OB projection neurons [Wachowiak, 2011] and the emergence of ketamine-dependent fast rhythms.…”
Section: Discussionsupporting
confidence: 91%
“…CSD and MUA analyses strongly suggest that mitral/tufted cells are involved in the generation of 80–130 Hz rhythm, consistent with our finding after ketamine in freely moving rats [Hunt et al, 2019]. Excitation, inhibition and gap junctions can all underlie mechanisms of fast oscillatory activity in the brain [Grenier et al, 2001].…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Also, as described before (Cavelli et al, 2018), a narrow peak in HFO at ≈ 130 Hz can be appreciated during REM sleep in the OB and sensory cortices (signaled with red arrows in Figure 2). HFO is implicated in the sensory processing (Bauer et al, 2014), and a recent study suggest that the OB is a source of HFO (Hunt et al, 2019). However, the whole HFO band power was not significantly different between NREM and REM sleep, probably because the set of frequencies involved in the peak is much narrower than the whole band.…”
Section: Ieeg Powermentioning
confidence: 94%
“…Ketamine, a psychoactive compound, has been widely reported to induce abnormal HFO in freely moving rodents (Hunt et al 2006;Cordon et al 2015;Caixeta et al 2013;Pittman-Polletta et al 2018). Recent work suggests the OB is an important generator of this activity, which can impose this activity in ventral striatal areas (Hunt et al 2019). In the OB, it is well-established that theta can couple to gamma oscillations (40-80 Hz) (for review see (Kay 2014)).…”
Section: Recordings From Rats After Ketamine Injectionmentioning
confidence: 99%